(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research presents a meticulous analysis of pollen grains obtained from various Rosa indica cultivars, encompassing 50 distinct species within the Rosaceae family. The study includes comprehensive descriptions of pollen grain characteristics, such as size, shape, and ornamentation, with accompanying imagery captured using light microscopy.